Progressive cholestasis and associated sclerosing cholangitis are frequent complications of COVID‐19 in patients with chronic liver disease. Issue 6 (18th June 2022) - Hartl, Lukas; Haslinger, Katharina; Angerer, Martin; Semmler, Georg; Schneeweiss‐Gleixner, Mathias; Jachs, Mathias; Simbrunner, Benedikt; Bauer, David Josef Maria; Eigenbauer, Ernst; Strassl, Robert; Breuer, Monika; Kimberger, Oliver; et al.
Abstract: Background and Aims: Cholestasis is associated with disease severity and worse outcome in COVID‐19. Cases of secondary sclerosing cholangitis (SSC) after severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection have been described. Approach and Results: Hospitalized patients with COVID‐19 between 03/2020 and 07/2021 were included. Patients were stratified as having (i) no chronic liver disease (CLD), (ii) non‐advanced CLD (non‐ACLD), or (iii) advanced CLD (ACLD). Patients with CLD and non–COVID‐19 pneumonia were matched to patients with CLD and COVID‐19 as a control cohort. Liver chemistries before (Pre) and at first, second, and third blood withdrawal after SARS‐CoV‐2 infection (T1–T3) and at last available time point (last) were recorded. A total of 496 patients were included. In total, 13.1% ( n  = 65) had CLD (non‐ACLD: 70.8%; ACLD: 29.2%); the predominant etiology was NAFLD/NASH (60.0%). COVID‐19–related liver injury was more common among patients with CLD (24.6% vs. 10.6%; p  = 0.001). After SARS‐CoV‐2 infection, patients with CLD exhibited progressive cholestasis with persistently increasing levels of alkaline phosphatase (Pre: 91.0 vs. T1: 121.0 vs. last: 175.0 U/L; p  < 0.001) and gamma‐glutamyl transferase (Pre: 95.0 vs. T1: 135.0 vs. last: 202.0 U/L; p  = 0.001). A total of 23.1% of patients with CLD ( n  = 15/65) developed cholestatic liver failure (cholestasis plus bilirubin ≥6 mg/dl) during COVID‐19, and 15.4% of patients ( n  = 10/65) developed SSC. SSC was significantly more frequent among patients with CLD and COVID‐19 than in patients with CLD and non–COVID‐19 pneumonia ( p  = 0.040). COVID‐19–associated SSC occurred predominantly in patients with NAFLD/NASH and metabolic risk factors. A total of 26.3% ( n  = 5/19) of patients with ACLD experienced hepatic decompensation after SARS‐CoV‐2 infection. Conclusions: About 20% of patients with CLD develop progressive cholestasis after SARS‐CoV‐2 infection. Patients with NAFLD/NASH and metabolic risk factors are at particular risk for developing cholestatic liver failure and/or SSC after COVID‐19. Abstract : The left panel depicts the trajectory of alkaline phosphatase (ALP) in chronic liver disease (CLD) patients with COVID‐19 before (Pre), at the first, second and third blood withdrawal after (T1–T3) SARS‐CoV‐2 infection and at the last available time point (last). The middle panel shows a coronal MIP MRCP image of a CLD patient with COVID‐19 exhibiting a "beaded" appearance of intrahepatic bile ducts due to alternating strictures and dilatation, as well as a filling defect in the distal common bile duct due to stones. The right panel depicts the comparison of the percentage of patients developing secondary sclerosing cholangitis between CLD patients with non–COVID‐19 pneumonia and CLD patients with COVID‐19.image